Unlocking SME investment potential: The determinants of an effective credit guarantee scheme in Morocco - Oussouadi Kamal; Cherkaoui Kenza (Investment Management & Financial Innovations)
This research seeks to identify the factors influencing the investment potential of SMEs following their receipt of government-guaranteed loans. To this end, an empirical methodology based on the statistical analysis of data collected from a representative sample of Moroccan companies was employed. This sample of 335 SMEs that had benefited from loans with government guarantees was selected at random to ensure its relevance to the population of SMEs in Morocco. The methodological approach is based on a regression analysis using the robust least squares (RLS) method. Firm profitability is positively related to higher investment, suggesting that government guarantees should encourage investment by profitable SMEs. Liquidity, repayment capacity and indebtedness at the time of applying for finance do not appear to influence investment. These elements can be improved after financing, which indicates that government guarantees should not penalize SMEs in difficulty. Decision-making maturity has a negative effect on investment, suggesting that young companies and entrepreneurs tend to invest more. A negative correlation is observed between company size and investment, which suggests that government guarantees should be geared towards small SMEs and young companies and entrepreneurs. Finally, managers with a large share of capital invest more, leading us to believe that government guarantees should favor this type of SME.